Procedures for Territorial Division of Medical Universities and Architectural Planning of Small Landscapes - Anvarovna, Nazarova Dinara; A., Khatamova P.; А., Zokirova L. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article examines the procedures for the territorial division of medical universities, the architectural planning of small landscapes in medical educational institutions, the use of compositional and memorial landscape solutions, issues and their importance in the educational process.